Interspeech 2017 2017
DOI: 10.21437/interspeech.2017-367
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness of French Voices for German Listeners — Results from Native and Non-Native Read Speech

Abstract: This study investigated how the perceived attractiveness of voices was influenced by a foreign language, a foreign accent, and the level of fluency in the foreign language. Stimuli were taken from a French-German corpus of read speech with German native speakers as raters. Additional factors were stimulus length (syllable or entire sentence) and sex (of the raters and speakers). Results with German native raters reveal that stimuli spanning just a syllable were judged significantly less attractive than those c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…On the other hand, calm-style advertisements may form an exotic contrast with advertisements on Russian-language radio (cf. Trouvain and Zimmerer, 2017). Further research could show which styles are present in Russian radio advertisements, and which are preferred by listeners in Russia.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, calm-style advertisements may form an exotic contrast with advertisements on Russian-language radio (cf. Trouvain and Zimmerer, 2017). Further research could show which styles are present in Russian radio advertisements, and which are preferred by listeners in Russia.…”
Section: Discussionmentioning
confidence: 96%
“…Likability was dependent on speech style: both Estonians and Finns preferred the voices in Estonian interviews and Finnish poetry readings. Some studies have revealed a preference for culturally familiar performance styles, a phenomenon known as the similarity-attraction effect (Dahlbäck et al, 2007) and others, the reverse (Trouvain and Zimmerer, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, listening to his brother speaking a foreign language (English) sounded to him oddly pleasant. Trouvain and Zimmerer (2017) reported that hearing the "voice" of a foreign language can attract learners and heighten their interest in the language. The charm of English sounds voiced by his brother attracted Amin to English.…”
Section: Informal English Language Learning Through the Zone Of Free mentioning
confidence: 99%